How Much Child Sexual Abuse is “Below the Surface,” and Can We Help Adults Identify it Early? - Martin, Erin K.; Silverstone, Peter H. (Frontiers in Psychiatry, 2013)
Child sexual abuse (CSA) occurs frequently in society to children aged between 2 – 17. It is significantly more common in girls than boys, with the peak age for CSA occurring when girls are aged 13-17. Many children experience multiple episodes of CSA, as well as having high rates of other victimizations (such as physical assaults). One of the problems for current research in CSA is different definitions of what this means, and no recent review has clearly differentiated more severe forms of CSA, and how commonly this is disclosed. In general we suggest there are four types of behaviour that should be included as CSA, namely (1) non-contact, (2) genital touching, (3) attempted vaginal and anal penetrative acts, and (4) vaginal and anal penetrative acts. Evidence suggests that CSA involving types (2), (3), and (4) is more likely to have significant long-term outcomes, and thus can be considered has having higher-impact. From the research to date approximately 15% of girls aged 2-17 experience higher-impact CSA (with most studies suggesting that between 12 – 18% of girls experience higher-impact CSA). Approximately 6% of boys experience higher-impact CSA (with most studies suggesting that between 5 – 8% experience higher-impact CSA). The data also suggests that in over 95% of cases the CSA is never disclosed to authorities. Thus, CSA is frequent but often not identified, and occurs “below the surface” in the vast majority of higher-impact cases. Helping adults to understand “below the surface” CSA might help them to recognize it early, but there are very few indicators specific to CSA, making this a challenging goal to achieve. Nonetheless, given that CSA frequently occurs with other types of abuse, a training program that focuses on both CSA and other abuse may offer a method to allow both early recognition and prevention by adults in the general population.